Kapocs - Moharos, Attila (Centrál Filmstúdió, 2009)
Verzio FF Submission Gabriela Lakatos was born in a Roma village. At an early age she realized she wanted more from life than her village could offer so she immersed herself in her studies. This film is the portrait of this ambitious woman who studied theology and became a successful missionary and a priest, a woman dedicated to saving souls, regardless of their race, ethnicity or social status.